POLITIK HUKUM PENGATURAN JABATAN WAKIL KEPALA DAERAH DALAM SISTEM DESENTRALISASI - Gugun El Guyanie (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
Constitutional desain which regulate the principle of district goverment with decentralization system give freedom to point out the vise of every district. But there is problem of disharmony because the conflict of authority. How is the significance vice district in the presidential system? How the politic of law regulate the ideal of vice district position? So Ideally the vice elected by the head of the district not elected by people of the region. The distribution of duty and authority between the head and his vice should be clear to avoid overlapping among them. The vice truly become the vice and responsible for the head of the district.